Research on the Properties of Polysaccharides, Starch, Protein, Pectin, and Fibre in Food Processing - Xie, Jianhua; Zhang, Yanjun; Yu, Hansong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the continuous improvement of people's living standards, the concern for food nutrition and safety has gradually increased. Consumers increasingly need to replace synthetic food additives with natural components extracted from food. Polysaccharides, starch, protein, pectin, and fibre are major types of biopolymer components in foods. They not only provide people with energy and nutrition, but are also used in food processing as natural additives due to their gelling, emulsifying, and film-forming properties, etc. They are characterised by high biocompatibility, low cost, and ease of access. Some natural components isolated from raw food materials have some drawbacks, such as low solubility and instability under certain conditions, which limit their application in food processing. Currently, many researchers are focusing on the modification, food technology, and future industry of polysaccharides, starch, protein, etc. These studies help to obtain the changed physicochemical and enhanced functional properties of these components, and further promote their high-value utilization in the food field. This Special Issue brings together 34 articles regarding the latest advances in the properties of polysaccharides, starch, protein, pectin, and fibre in food processing, from the improvements of the physical properties of major food components and biological activity studies to their applications in food preservation.